Description of Risk Factors for Coronary Heart Disease at the Family Medical Center Hospital Heart Clinic In 2021 - Kurniadhi, Didi; Masiku, Gabriela Limbong; Sari, Monica Puspa (GoAcademica Research & Publishing, 2024)
Coronary heart disease (CHD) is a condition of reduced blood and oxygen supply to the heart muscle due to blockage by plaque in the blood vessels, called atherosclerosis. CHD is a health burden in the world because it contributes to high mortality rates, including in Indonesia according to Riskesdas 2018. This research aims to determine the description of risk factors for coronary heart disease at the Family Medical Center Hospital Heart Clinic in 2021. This research uses a descriptive survey method with a cross-sectional approach. The total population was 369 and the sample using the total sampling technique obtained 318 people who met the inclusion criteria. The research results showed that the largest age distribution was in the 60-69 year age range, as many as 111 people (34.9%), the largest gender was female, 165 people (51.9%), 15 people (4.7%) had a family history, hypertension 109 people (34.3%), diabetes mellitus 125 people (39.3%), dyslipidemia 201 people (70.4%), smoking 63 people (19.8%), overweight and obesity 224 people (70.3%). CHD patients at the Family Medical Center Hospital Heart Clinic are mostly aged 60-69 years, female, most have no family history, have dyslipidemia, have a BMI in the overweight and obese categories, most did not have a history of hypertension, did not have Diabetes Mellitus, and most did not smoke.